Iron phosphate material uniformly doped with titanium element and preparation method of iron phosphate material

By controlling the pH value and input method in the liquid phase synthesis stage of iron phosphate, uniform doping of titanium elements is achieved, the problems of uneven doping and complex process in the existing technology are solved, and the electrochemical performance of lithium iron phosphate is improved and compaction density.

CN119218954APending Publication Date: 2024-12-31ZHEJIANG YOUSHAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411391985.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the doping process of titanium elements in lithium iron phosphate materials has problems such as harsh reaction conditions and uneven doping, resulting in unstable electrical performance, complex process and high energy consumption.

Method used

By adding titanium salt solution in the liquid phase synthesis stage of iron phosphate, and controlling the reaction pH value within the range of 1.0-2.5, two strands are used to put the titanium salt and phosphate-oxygen mixture to ensure uniform doping of titanium elements. Simplify process flow and reduce energy consumption.

Benefits of technology

The uniform doping of titanium elements is achieved, the production process is simplified, the crystal structure of iron phosphate is improved, the electrochemical performance and compaction density of lithium iron phosphate is significantly improved, and the production cycle is shortened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218954A_ABST
    Figure CN119218954A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an iron phosphate material uniformly doped with a titanium element. The preparation method comprises the following steps: S1, respectively preparing a phosphoric acid solution, a phosphorus-oxygen mixed solution, a ferrous sulfate salt solution and a titanium salt solution; s2, adjusting the pH value of the ferrous sulfate salt solution to 1.0-2.5, adding the titanium salt solution and the phosphorus-oxygen mixed solution in a two-strand simultaneous adding manner, uniformly stirring, and reacting for 25-35 minutes at the temperature of 30-60 DEG C to obtain slurry A; s3, filtering and washing the slurry A to obtain a filter cake B; s4, adding water into the filter cake B, pulping, adding a phosphoric acid solution, heating, and preserving heat to obtain white slurry B; s5, filtering, washing and drying the white slurry B to obtain titanium-doped iron phosphate dihydrate, and calcining the iron phosphate dihydrate to obtain anhydrous iron phosphate; according to the invention, the crystal structure of the iron phosphate is improved by doping the titanium element, short-range preparation of the iron phosphate is realized, uniform doping of the element is ensured, the production period is shortened, and the complexity of the process is obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to an iron phosphate material uniformly doped with titanium and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of my country's new energy vehicle industry, the demand for lithium-ion power batteries has continued to increase, among which the installed capacity of power batteries using lithium iron phosphate as the positive electrode material has gradually increased, and the lithium iron phosphate market has developed rapidly. Lithium iron phosphate has the advantages of low cost, good safety, strong thermal stability, and long cycle life, but its disadvantages such as low electronic conductivity, slow lithium ion transmission speed, and low theoretical capacity seriously restrict its application in high-power occasions.

[0003] The main methods to improve the electronic conductivity of lithium iron phosphate and the speed of lithium ion transmission include metal ion doping, surface carbon coating, and reducing particle size. Metal ion doping is a common method to improve the conductivity of lithium iron phosphate. Doping with high-valent cations can produce p-type semiconductors, improve conductivity, and reduce activation energy, which can effectively improve the rate performance of lithium iron phosphate. The current main doping method is to add additives during wet mixing and achieve the doping effect with the help of subsequent high-temperature sintering steps. Limited by the high-temperature solid-phase sintering preparation process, doping needs to be carried out at high temperature, which requires more energy consumption and the uniformity of doping is difficult to guarantee.

[0004] Iron phosphate is the precursor of lithium iron phosphate, and its physical and chemical indicators will significantly affect the compaction density and electrical properties of lithium iron phosphate. Advancing the doping from lithium iron phosphate to the liquid phase synthesis stage of iron phosphate can improve the uniformity of doping, while reducing energy consumption and facilitating industrialization. Commonly used doping elements include titanium, vanadium, aluminum, etc. The relevant technical solutions are briefly described as follows: The patent "A method for preparing titanium-doped iron phosphate by wet method, CN 111908441 A" discloses a method for preparing titanium-doped iron phosphate. The method adopts a coating coprecipitation method, adds saturated titanium salt to the iron salt solution, and controls the precipitation order of titanium salt and iron phosphate by controlling the pH of the system, thereby achieving the effect of iron phosphate coating and precipitation on the surface of titanium salt.

[0005] The patent "Titanium-doped battery-grade iron phosphate and its preparation method, CN 115818601 A" discloses a method for preparing titanium-doped iron phosphate. Add iron-containing titanium ore to an unremoved ferrous sulfate solution to obtain a first mixed system, and control the addition rate of the titanium-containing iron ore to control the doping amount of Ti; then add it to the reaction vessel in a split flow with the phosphate solution to obtain a second mixed system, and then add a catalyst, and pass an oxygen-containing gas to perform a catalytic oxidation reaction to obtain a third mixed system. After washing and drying, iron phosphate is obtained. After the iron phosphate prepared by this method is made into lithium iron phosphate, the compaction density is 2.4 g / cm3, and the 1C discharge specific capacity is 146.6 mAh / g.

[0006] The patent "A method for preparing low-cost iron phosphate, CN 111422845 B" discloses a method for preparing vanadium-doped iron phosphate. Ferric chloride, vanadium chloride and phosphoric acid are used as raw materials. The three raw materials are added to a reactor at the same time and the temperature is raised. The pH of the system is regulated by reduced pressure evaporation. During the pH increase, Fe3+ and V3+ are precipitated in the form of phosphate to generate vanadium-doped iron phosphate.

[0007] "A method for preparing doped iron phosphate by comprehensive utilization of vanadium-titanium iron ore, CN 116553500 A" uses vanadium-titanium iron ore as raw material to prepare titanium-aluminum co-doped iron phosphate. After lithium iron phosphate is made, the 0.1C charge-discharge specific capacity is 160 mAh / g.

[0008] However, the reaction conditions of the above technology are harsh, and the precipitation rate of the doping elements cannot be controlled, resulting in the disadvantage of uneven doping, which in turn causes the electrical performance of lithium iron phosphate to decrease instead of increase.

[0009] For example, the patent "A method for preparing titanium-doped iron phosphate by wet method, CN 111908441 A" has the problem of harsh reaction conditions. The patent first controls the iron source and phosphorus source to react for a long time (3-5 h) in a low pH system (pH <1), then filters, adds saturated titanium salt to the obtained clear solution, oxidizes for 0.75-1.25 h, adjusts the pH to 1.2-1.8, reacts at high temperature for 1-4 h, and obtains titanium-doped iron phosphate material after washing, drying, and calcining.

[0010] The patent "Titanium-doped battery-grade iron phosphate and its preparation method, CN 115818601 A" has the disadvantages of uncontrollable reaction, uneven doping, and uncontrollable doping amount. The iron-containing titanium ore is quickly added to the ferrous sulfate solution, and three reactions occur simultaneously in the system: ① The iron element reduces part of TiO2 to Ti3+ ions, so that Ti3+ is evenly distributed in the ferrous sulfate solution, avoiding the complete hydrolysis of Ti and reducing the Ti doping amount; ② The iron element reduces Fe3+; ③ The iron element increases the pH of the system and removes impurities such as Mg and Al in the ferrous sulfate solution. The extent of the above three reactions is difficult to control, and the stability of the system is difficult to guarantee. At the same time, the reaction also requires the additional addition of sodium nitrite catalyst, which increases the cost of water treatment.

[0011] The patent "A low-cost method for preparing iron phosphate, CN 111422845 B" also has the problem of uneven doping. The system controls the change of the system pH by evaporation under reduced pressure. During the process of increasing pH, V3+ can easily combine directly with phosphate to form vanadium phosphate, or combine with iron to form iron vanadate.

[0012] The patent "A method for preparing doped ferric phosphate by comprehensive utilization of vanadium-titanium iron ore, CN 116553500 A" directly uses vanadium-titanium iron ore to prepare ferric phosphate, and controls the amount of titanium added by controlling the pH of the system and the time of the reduction reaction. This is difficult to control and there is a risk of simultaneous precipitation of vanadium, titanium and iron. Summary of the invention

[0013] In order to solve the above technical problems, the present invention provides a titanium-uniformly doped iron phosphate material and a preparation method thereof, which are as follows: A method for preparing a titanium-uniformly doped iron phosphate material comprises the following steps: S1, respectively prepare phosphoric acid solution, phosphorus oxygen mixed solution, ferrous sulfate solution, titanium salt solution, and set aside; the phosphorus oxygen mixed solution is a mixed solution of phosphorus salt solution and hydrogen peroxide solution, and the mass ratio of the phosphorus salt solution to the hydrogen peroxide solution is 1:0.5-0.8; S2. Adjust the pH value of the ferrous sulfate solution to 1.0-2.5, add the titanium salt solution and the phosphorus oxygen mixed solution in two streams, stir evenly, control the reaction temperature to 30-60°C, and react for 25-35 min to obtain slurry A; S3, slurry A is filtered and washed to obtain filter cake B; S4, add water to the filter cake B to make a slurry, add phosphoric acid solution, and heat the slurry to 80-100°C under continuous stirring, and keep it warm for 1-2 hours to obtain a white slurry B; S5. The white slurry B is filtered, washed and dried to obtain titanium-doped iron phosphate dihydrate. The iron phosphate dihydrate is calcined to obtain anhydrous iron phosphate.

[0014] Preferably, in step S1, the concentration of the phosphoric acid solution is 40-85wt%; and the concentration of phosphorus in the phosphate solution is 0.5-1.5 mol / L.

[0015] Preferably, in step S1, the concentration of the iron element in the ferrous sulfate solution is 0.5-1.5 mol / L, and the concentration of the hydrogen peroxide solution is 25-35wt%.

[0016] Preferably, in step S2, the molar ratio of iron element to phosphorus element in the ferrous sulfate solution and the phosphate solution is controlled to be 1:0.9-1:1.2.

[0017] Preferably, in step S2, the pH value of the ferrous sulfate solution is controlled by sulfuric acid solution, liquid alkali or ammonia solution. When the pH is greater than 2.5, a certain amount of sulfuric acid solution is added; when the pH is less than 1.0, a certain amount of liquid alkali or ammonia solution is added.

[0018] Preferably, in step S1, the phosphate salt solution is prepared from any one of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate; the titanium salt solution is prepared from raw materials such as titanium dioxide, titanium sulfate, titanyl sulfate, titanium nitrate, and titanium tetrachloride; and the ferrous sulfate solution is prepared from ferrous sulfate, ferrous nitrate, and ferrous chloride.

[0019] Preferably, in step S1, the phosphate salt solution is prepared from phosphoric acid, and during the preparation, ammonia water or liquid alkali is added to adjust the pH value thereof to 3-8.

[0020] Preferably, in step S4, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution is n(P):n(Fe)=0.1-0.9:1.

[0021] On the other hand, the present invention provides a method for preparing a titanium-uniformly doped iron phosphate material. The titanium-doping amount of the prepared titanium-uniformly doped iron phosphate material is 100-3000 ppm.

[0022] Preferably, the iron-to-phosphorus ratio of the ferric phosphate material is 95-98.

[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. Compared with the existing preparation technology of iron phosphate, the present invention improves the crystal structure of iron phosphate by doping with titanium, realizes the short-range preparation of iron phosphate, ensures the uniform doping of elements, shortens the production cycle, and significantly reduces the complexity of the process.

[0024] 2. The present invention provides a titanium-uniformly doped iron phosphate material and a preparation method thereof. The reaction conditions are simple. It is only necessary to add a titanium salt solution in the synthesis stage, and uniform doping of the element can be achieved by controlling the process pH. The principle is that the present invention adopts an iron salt as the base, and a titanium salt solution and a phosphorus oxygen mixed solution (a mixed solution of a phosphorus salt solution and a hydrogen peroxide solution) are added in parallel for preparation, and the pH of the iron salt solution is controlled to be 1.0-2.5; when the phosphate radical is excessive, the titanium ion will directly combine with the phosphate radical to form a titanium phosphate precipitate; when the pH>2.5, the titanium ion is very easy to hydrolyze to form a metatitanic acid precipitate; both of the above situations are not conducive to achieving uniform doping of the titanium element; the present invention controls the pH of the base solution to be 1.0-2.5, controls the titanium element and the phosphorus salt to be added in parallel, so as to ensure a low degree of hydrolysis of titanium, and does not generate a titanium phosphate precipitate, effectively inhibits the hydrolysis and precipitation of titanium ions, and allows the titanium element to be incorporated into the iron phosphate lattice in the form of ions, thereby achieving uniform doping. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the EDS image of the anhydrous iron phosphate prepared in Experiment 1 of the present invention. DETAILED DESCRIPTION

[0026] Example 1 A method for preparing a titanium-uniformly doped iron phosphate material comprises the following steps: S1. Prepare phosphoric acid solution, phosphorus-oxygen mixed solution, ferrous sulfate solution and titanium salt solution respectively for standby use; the phosphorus-oxygen mixed solution is a mixed solution of phosphorus salt solution and hydrogen peroxide solution, and the mass ratio of the phosphorus salt solution to the hydrogen peroxide solution is 1:0.5; S2. Adjust the pH value of the ferrous sulfate solution to 1.0-2.5, add the titanium salt solution and the phosphorus oxygen mixed solution in two streams, stir evenly, control the reaction temperature to 30°C, and react for 25 minutes to obtain slurry A; S3, slurry A is filtered and washed to obtain filter cake B; S4, add water to the filter cake B to make a slurry, add phosphoric acid solution, and heat the slurry to 80°C under continuous stirring, and keep it warm for 1 hour to obtain a white slurry B; S5. The white slurry B is filtered, washed and dried to obtain titanium-doped iron phosphate dihydrate. The iron phosphate dihydrate is calcined to obtain anhydrous iron phosphate.

[0027] Moreover, in the step S1, the concentration of the phosphoric acid solution is 40wt%; and the concentration of phosphorus in the phosphate solution is 0.5 mol / L.

[0028] Moreover, in the step S1, the concentration of the iron element in the ferrous sulfate solution is 0.5 mol / L, and the concentration of the hydrogen peroxide solution is 25 wt %.

[0029] Moreover, in step S2, the molar ratio of iron element to phosphorus element in the ferrous sulfate solution and the phosphate solution is controlled to be 1:0.9.

[0030] Moreover, in step S2, the pH value of the ferrous sulfate solution is controlled by sulfuric acid solution, liquid alkali or ammonia solution. When the pH is greater than 2.5, a certain amount of sulfuric acid solution is added; when the pH is less than 1.0, a certain amount of liquid alkali or ammonia solution is added.

[0031] Moreover, in the step S1, the phosphate salt solution is prepared from any one of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate; the titanium salt solution is prepared from raw materials such as titanium dioxide, titanium sulfate, titanyl sulfate, titanium nitrate, and titanium tetrachloride; and the ferrous sulfate solution is prepared from ferrous sulfate, ferrous nitrate, and ferrous chloride.

[0032] Preferably, in step S1, the phosphate salt solution is prepared from phosphoric acid, and during the preparation, ammonia water or liquid alkali is added to adjust the pH value thereof to 3.

[0033] Preferably, in step S4, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution is n(P):n(Fe)=0.1:1.

[0034] Example 2 A method for preparing a titanium-uniformly doped iron phosphate material comprises the following steps: S1. Prepare phosphoric acid solution, phosphorus-oxygen mixed solution, ferrous sulfate solution and titanium salt solution respectively for standby use; the phosphorus-oxygen mixed solution is a mixed solution of phosphorus salt solution and hydrogen peroxide solution, and the mass ratio of the phosphorus salt solution to the hydrogen peroxide solution is 1:0.8; S2. Adjust the pH of the ferrous sulfate solution to 1.0-2.5, add the titanium salt solution and the phosphorus oxygen mixed solution in two streams, stir evenly, control the reaction temperature to 60°C, and react for 35 min to obtain slurry A; S3, slurry A is filtered and washed to obtain filter cake B; S4, add water to the filter cake B to make a slurry, add phosphoric acid solution, and heat the slurry to 100°C under continuous stirring, and keep it warm for 2 hours to obtain a white slurry B; S5. The white slurry B is filtered, washed and dried to obtain titanium-doped iron phosphate dihydrate. The iron phosphate dihydrate is calcined to obtain anhydrous iron phosphate.

[0035] Moreover, in the step S1, the concentration of the phosphoric acid solution is 85wt%; and the concentration of phosphorus in the phosphate solution is 1.5 mol / L.

[0036] Moreover, in the step S1, the concentration of the iron element in the ferrous sulfate solution is 1.5 mol / L, and the concentration of the hydrogen peroxide solution is 35 wt %.

[0037] Moreover, in step S2, the molar ratio of iron element to phosphorus element in the ferrous sulfate solution and the phosphate solution is controlled to be 1:1.2.

[0038] Moreover, in step S2, the pH value of the ferrous sulfate solution is controlled by sulfuric acid solution, liquid alkali or ammonia solution. When the pH is greater than 2.5, a certain amount of sulfuric acid solution is added; when the pH is less than 1.0, a certain amount of liquid alkali or ammonia solution is added.

[0039] Moreover, in the step S1, the phosphate salt solution is prepared from any one of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate; the titanium salt solution is prepared from raw materials such as titanium dioxide, titanium sulfate, titanyl sulfate, titanium nitrate, and titanium tetrachloride; and the ferrous sulfate solution is prepared from ferrous sulfate, ferrous nitrate, and ferrous chloride.

[0040] Preferably, in step S1, the phosphate salt solution is prepared from phosphoric acid, and during the preparation, ammonia water or liquid alkali is added to adjust the pH value thereof to 8.

[0041] Preferably, in step S4, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution is n(P):n(Fe)=0.9:1.

[0042] Example 3 A method for preparing a titanium-uniformly doped iron phosphate material comprises the following steps: S1, respectively prepare phosphoric acid solution, phosphorus oxygen mixed solution, ferrous sulfate solution, titanium salt solution, and set aside; the phosphorus oxygen mixed solution is a mixed solution of phosphorus salt solution and hydrogen peroxide solution, and the mass ratio of the phosphorus salt solution to the hydrogen peroxide solution is 1:0.65; S2, adjusting the pH of the ferrous sulfate solution to 1.0-2.5, adding the titanium salt solution and the phosphorus oxygen mixed solution in two streams, stirring evenly, controlling the reaction temperature to 45°C, and reacting for 30 min to obtain slurry A; S3, slurry A is filtered and washed to obtain filter cake B; S4, add water to the filter cake B to make a slurry, add phosphoric acid solution, and heat the slurry to 90° C. under continuous stirring, and keep the temperature for 1.5 hours to obtain a white slurry B; S5. The white slurry B is filtered, washed and dried to obtain titanium-doped iron phosphate dihydrate. The iron phosphate dihydrate is calcined to obtain anhydrous iron phosphate.

[0043] Moreover, in the step S1, the concentration of the phosphoric acid solution is 40-85wt%; the concentration of phosphorus in the phosphate solution is 1 mol / L.

[0044] Moreover, in the step S1, the concentration of the iron element in the ferrous sulfate solution is 1 mol / L, and the concentration of the hydrogen peroxide solution is 30 wt %.

[0045] Moreover, in step S2, the molar ratio of iron element to phosphorus element in the ferrous sulfate solution and the phosphate solution is controlled to be 1:1.

[0046] Moreover, in step S2, the pH value of the ferrous sulfate solution is controlled by sulfuric acid solution, liquid alkali or ammonia solution. When the pH is greater than 2.5, a certain amount of sulfuric acid solution is added; when the pH is less than 1.0, a certain amount of liquid alkali or ammonia solution is added.

[0047] Moreover, in the step S1, the phosphate salt solution is prepared from any one of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate; the titanium salt solution is prepared from raw materials such as titanium dioxide, titanium sulfate, titanyl sulfate, titanium nitrate, and titanium tetrachloride; and the ferrous sulfate solution is prepared from ferrous sulfate, ferrous nitrate, and ferrous chloride.

[0048] Preferably, in step S1, the phosphate salt solution is prepared from phosphoric acid, and during the preparation, ammonia water or liquid alkali is added to adjust the pH value thereof to 5.

[0049] Preferably, in step S4, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution is n(P):n(Fe)=0.5:1.

[0050] Experimental Section

[0051] Experiment 1 This experiment adopts the technical solution of the present invention, a method for preparing a titanium-element uniformly doped iron phosphate material: (1) Weigh 552 g of ammonium dihydrogen phosphate and dissolve it, add 300 g of 30 wt% hydrogen peroxide and dilute to 4 L to obtain a mixed solution of phosphate and hydrogen peroxide; weigh 1334 g of ferrous sulfate heptahydrate and dissolve it and dilute to 4 L to obtain a ferrous salt solution; weigh 3.6 g of titanium sulfate and dissolve it in water to obtain a titanium sulfate solution.

[0052] (2) The pH of the ferrous salt solution was controlled at 2.0, and titanium sulfate solution and phosphorus oxide mixed solution were added at the same time. The feeding time was controlled to be 30 min. After the feeding, the mixture was reacted for 30 min to obtain slurry C.

[0053] (3) The slurry is washed and filtered to obtain a filter cake.

[0054] (4) Add pure water for slurrying, add 330 g of 80 wt% phosphoric acid, raise the temperature to 85 °C, and keep warm for 2 h to obtain a white slurry.

[0055] (5) After filtering, washing and drying the slurry, ferric phosphate dihydrate is obtained.

[0056] (6) After calcination, dihydrate iron phosphate is obtained to obtain anhydrous iron phosphate.

[0057] The obtained anhydrous iron phosphate was analyzed by energy dispersive X-ray spectroscopy (EDS). The EDS graph of iron phosphate is shown in Figure 1 As shown, take Figure 1 The EDS data of Spectrurm 1-Spectrurm 5 (Table 1) show that the titanium content at each scanning point is close, indicating that the titanium is uniformly incorporated.

[0058] Table 1 EDS data of Example 1

[0059] Experiment 2 This experiment adopts the technical solution of the present invention and is carried out according to the method described in Experiment 1, except that 4.8 g of titanyl sulfate is weighed in step (1).

[0060] Experiment 3 This experiment was carried out according to the method described in Experiment 1, except that no titanium sulfate solution was added in step (2).

[0061] Experiment 4 This experiment was carried out according to the method described in Experiment 1, except that in step (2), the titanium sulfate solution was added first, and then the phosphorus-oxygen mixed solution was added in a single stream.

[0062] Experiment 5 This experiment was carried out according to the method described in Experiment 1, except that in step (2), the phosphorus-oxygen mixed solution was first added in a single stream, and then the titanium sulfate solution was immediately added.

[0063] 1. Determination of finished product indicators The anhydrous ferric phosphate prepared in Experiments 1-5 was tested for Fe content, P content, H2O content, Fe / P, D50 (particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 50%), BET (specific surface area), tap density (TD), and Ti concentration, see Table 2.

[0064] Table 2 Finished product indicators

[0065] As can be seen from Table 2, compared with the undoped sample (Experiment 3), the Fe / P, H2O, D50, BET, TD and other indicators of the samples prepared by the present invention (Experiment 1, Experiment 2) have no obvious changes, and the titanium element yield is close to 100%; the Fe content of Experiment 4 is low, because the titanium element occupies the iron position under this feeding method; although the Fe / P, H2O, D50, TD and other indicators of Experiment 5 are normal, BET is significantly reduced; in summary, the method of using the titanium salt (titanium sulfate solution) and the phosphorus oxygen mixed solution of the present invention to feed together is the best.

[0066] 2. Determination of electrochemical properties of lithium iron phosphate and powder compaction density The anhydrous iron phosphate prepared in Experiments 1-5 was made into lithium iron phosphate material and button batteries. The electrochemical performance and powder compaction density were tested. The test results are shown in Table 3.

[0067] Table 3 Lithium iron phosphate performance test results

[0068] As can be seen from Table 3, after Experiment 1-2 used the iron phosphate prepared by the present invention to prepare lithium iron phosphate, the 1C discharge capacity was significantly improved, which was significantly higher than Experiment 3-5, and the powder compaction density was also higher than that of other experiments. The reasons are as follows: the titanium doping in Experiment 1-2 was relatively uniform, and the lithium iron phosphate inherited the uniformity of doping, and doping can effectively improve the electrical conductivity, so the electrical performance is improved; titanium doping can limit the growth of lithium iron phosphate particles to a certain extent, increase the proportion of small particles, and small particles fill the pores of large particles, so the compaction density is improved; the iron-phosphorus ratio in Experiment 4 is relatively low, resulting in poor compaction density and electrical properties; the specific surface area of ​​Experiment 5 is relatively low, and it is easier to produce large particles after being made into lithium iron, and the grading is poor, so the compaction density and electrical properties are poor.

Claims

1. A method for preparing a titanium-uniformly doped iron phosphate material, characterized in that: The following steps are involved: S1. Prepare phosphoric acid solution, phosphorus-oxygen mixed solution, ferrous sulfate solution and titanium salt solution respectively for standby use; The phosphorus-oxygen mixed solution is a mixed solution of a phosphate solution and a hydrogen peroxide solution, and the mass ratio of the phosphate solution to the hydrogen peroxide solution is 1:0.5-0.8; S2. Adjust the pH value of the ferrous sulfate solution to 1.0-2.5, add the titanium salt solution and the phosphorus oxygen mixed solution in two streams, stir evenly, control the reaction temperature to 30-60°C, and react for 25-35 min to obtain slurry A; S3, slurry A is filtered and washed to obtain filter cake B; S4, add water to the filter cake B to make a slurry, add phosphoric acid solution, and heat the slurry to 80-100°C under continuous stirring, and keep it warm for 1-2 hours to obtain a white slurry B; S5. The white slurry B is filtered, washed and dried to obtain titanium-doped iron phosphate dihydrate. The iron phosphate dihydrate is calcined to obtain anhydrous iron phosphate.

2. The method for preparing a titanium-uniformly doped iron phosphate material according to claim 1, characterized in that: In the step S1, the concentration of the phosphoric acid solution is 40-85wt%; the concentration of phosphorus in the phosphate solution is 0.5-1.5mol / L.

3. The method for preparing a titanium-uniformly doped iron phosphate material according to claim 1, characterized in that: In the step S1, the concentration of the iron element in the ferrous sulfate solution is 0.5-1.5 mol / L, and the concentration of the hydrogen peroxide solution is 25-35wt%.

4. The method for preparing a titanium-uniformly doped iron phosphate material according to claim 1, characterized in that: In step S2, the molar ratio of iron element to phosphorus element in the ferrous sulfate solution and the phosphate solution is controlled to be 1:0.9-1:1.

2.

5. The method for preparing a titanium-uniformly doped iron phosphate material according to claim 1, characterized in that: In step S2, the pH value of the ferrous sulfate solution is controlled by sulfuric acid solution, liquid alkali or ammonia solution. When the pH is greater than 2.5, a certain amount of sulfuric acid solution is added; when the pH is less than 1.0, a certain amount of liquid alkali or ammonia solution is added.

6. The method for preparing a titanium-uniformly doped iron phosphate material according to claim 1, characterized in that: In step S1, the phosphate solution is prepared from any one of ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and sodium phosphate; the titanium salt solution is prepared from raw materials such as titanium dioxide, titanium sulfate, titanyl sulfate, titanium nitrate, and titanium tetrachloride; and the ferrous sulfate solution is prepared from ferrous sulfate, ferrous nitrate, and ferrous chloride.

7. The method for preparing a titanium-uniformly doped iron phosphate material according to claim 1, characterized in that: In step S1, the phosphate solution is prepared from phosphoric acid, and during the preparation, ammonia water or liquid alkali is added to adjust the pH value thereof to 3-8.

8. The method for preparing a titanium-uniformly doped iron phosphate material according to claim 1, characterized in that: In step S4, the molar ratio of phosphorus in the phosphoric acid solution to iron in the slurry A solution is n(P):n(Fe)=0.1-0.9:

1.

9. The titanium-doped iron phosphate material uniformly prepared by the method for preparing a titanium-doped iron phosphate material uniformly according to any one of claims 1 to 8, wherein the doping amount of titanium is 100-3000 ppm.

10. The titanium-uniformly doped iron phosphate material according to claim 9, characterized in that: The iron-to-phosphorus ratio of the ferric phosphate material is 95-98.

Citation Information

Cited By

  • Preparation method of high-compaction titanium-doped iron phosphate

    CN120864463A

  • A method for preparing high-density titanium-doped iron phosphate

    CN120864463B

  • Method for preparing titanium-vanadium doped iron phosphate

    CN121974317A

  • A method for preparing titanium-vanadium doped iron phosphate

    CN121974317B

  • Iron phosphate material, and positive electrode material, preparation method therefor, and use thereof

    WO2026199607A1